Educação ambiental no ambiente escolar: os resíduos sólidos na Escola Municipal Clementino de Lima em Lajedo-PE - Rodrigues, Paula (2024)
Environmental education is an important process to promote awareness about the importance of environmental conservation and to encourage sustainable practices. Solid waste is material discarded by human activities that can cause negative impacts on the environment if not treated correctly. Thus, the search for effective solutions to the socio-environmental problems generated by the accumulation, destination and lack of adequate treatment of urban solid waste has sparked discussions, mobilizations and an intense search for alternatives with a view to achieving sustainable environmental balance. Therefore, this research seeks not only to expose these problems, but to find ideas in the relevant literature that contribute as alternatives to mitigating these obstacles. In this sense, the objective of this research is to investigate the effectiveness of Environmental Education practices, from the perspective of the Clementino Francisco de Lima Municipal School, in the city of Lajedo-PE, with an emphasis on raising awareness and sensitizing students regarding environmental issues. The research is based on a case study at the aforementioned school, aiming to evaluate the educational strategies employed, the involvement of students and the perception of teachers regarding the environment. Environmental education plays a fundamental role in the formation of conscious and responsible citizens, capable of contributing to the sustainability and preservation of the planet. Regarding the methodological procedures, we have: in relation to nature, this is an applied research, since it aims to build knowledge that can be used to solve possible problems generated by the inadequate disposal of packaging in the school community. Regarding the approach: The data collected with this research aims to describe the inappropriate disposal of solid waste in the surroundings of the school community. Regarding the objectives, it is characterized by being an exploratory and descriptive research. Exploratory because it seeks to explore a problem in order to provide information for a more precise and descriptive investigation because it will describe what happened during the study, since it aims to be closer to the theme. The product of the Dissertation will be, with the help of a didactic sequence on solid waste, the construction of a booklet on afforestation for the city of Lajedo, aiming to strengthen environmental education with students in the 5th year "A" of elementary school I.